PENGARUH PEMBANGUNAN INFRASTRUKTUR RUMAH RAKYAT TERHADAP PERTUMBUHAN EKONOMI MASYARAKAT DI DISTRIK PANTAI TIMUR BARAT KABUPATEN SARMI - Yong, Pieter Marvin; Rante, Harmonis; Rusim, Dewi Ana (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
The People's Home Infrastructure Development Program in Sarmi Regency began to be planned and carried out faster development penetration since Sarmi Regency was separated from the main Regency, namely Jayapura Regency in 2022 with the passing of Law Number: 26 of 2002. This research in the West East Coast District aims to know about the above and also know what obstacles occur in the field if the beneficiaries of the construction of people's housing infrastructure after receiving development assistance, their economic income conditions remain the same or increase or vice versa. The descriptive research method can also be described as a procedure for solving the problem being studied by describing or depicting the condition of the subject and research object of an institution, society and others. The form of this research will also begin with the research stage as the key to the research, followed by collecting data through several stages after which the data that has been collected will be analyzed in the form of a qualitative description in the form of meaning related to the problem being studied, namely the development of people's housing infrastructure and the economic conditions of the recipient community. assistance for public housing infrastructure in the East West Coast District, Sarmi Regency. The respondents who were the subjects of this research were people in the West East Coast District who received Assistance for People's Home Infrastructure Development from 2018-2022. Based on the data obtained, it is known that all variables have an AVE value of more than 0.5, but there are several indicators that measure a variable that has an outer loading of less than 0.5 (red writing).